Indonesian EFL Teacher Educators’ Beliefs and Classroom Practices on The Teaching of Pronunciation: Evidence from A Pilot Study - Yulia, Made Frida; Saukah, Ali (Universitas Negeri Malang, 2021)
Oral communication among global speakers needs good pronunciation to be successful. Regardless of its important function and role, EFL teachers often ignore pronunciation in their language teaching and oftentimes they are very lenient towards mispronunciation, which potentially hampers actual oral communication beyond language classrooms. An exploration into EFL teachers’ teaching beliefs is thus necessitated since such beliefs are mutually capable of influencing their classroom behaviors. In the effort to fill the gap of the previous research, the current study attempted to unveil teacher educators’ beliefs on teaching English pronunciation in Indonesian EFL context as well as to describe in what ways their classroom practices matched their beliefs. A qualitative research design using a semi-structured interview was employed to collect data from three Indonesian teacher educators who were experienced in teaching EFL. Similar findings to prior studies were discovered about their teaching beliefs, with one inconclusive issue remaining about teaching prioritization. Their classroom practices also generally went hand in hand with their underlying beliefs. One noteworthy finding that surfaced was the idea to have a dedicated English class for pronunciation, especially in the context of training prospective EFL teachers.